1998
DOI: 10.1530/eje.0.1390615
|View full text |Cite
|
Sign up to set email alerts
|

Variations in glucocorticoid levels within the physiological range affect plasma leptin levels

Abstract: Objective: Leptin, the obese gene product, is thought to regulate body fat through its action on hypothalamic receptors that influence satiety. The hormonal regulation of leptin is important, since it might affect adiposity. Leptin regulation in man is poorly understood. We studied the relation between endogenous cortisol and leptin levels as well as the acute and chronic effects of a low dose of dexamethasone (DEX) on plasma leptin levels in healthy male volunteers. Subjects and experimental protocol:The corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 42 publications
6
22
0
2
Order By: Relevance
“…The findings in this study support our previous report that glucocorticoids within the physiological range upregulate plasma leptin (13), as this was also noticed following the ingestion of a total of 0.4 mg DEX in the volunteers eating twice a day. In contrast, DEX did not increase leptin in those fasting for 48 h when compared with the control group.…”
Section: A Elimam and C Marcussupporting
confidence: 92%
See 2 more Smart Citations
“…The findings in this study support our previous report that glucocorticoids within the physiological range upregulate plasma leptin (13), as this was also noticed following the ingestion of a total of 0.4 mg DEX in the volunteers eating twice a day. In contrast, DEX did not increase leptin in those fasting for 48 h when compared with the control group.…”
Section: A Elimam and C Marcussupporting
confidence: 92%
“…In most studies, exogenous glucocorticoids are reported to upregulate leptin (11,13), but it has been questioned if the effect is limited to pharmacological dosing (31). The findings in this study support our previous report that glucocorticoids within the physiological range upregulate plasma leptin (13), as this was also noticed following the ingestion of a total of 0.4 mg DEX in the volunteers eating twice a day.…”
Section: A Elimam and C Marcussupporting
confidence: 86%
See 1 more Smart Citation
“…Glucocorticoids are potent stimulators of leptin secretion [13, 14, 15, 16, 17, 18, 19], and there is a reciprocal temporal relationship between circulating leptin and glucocorticoids [5, 20, 21]. The nocturnal increase in leptin, when compared as 24-hour secretory profiles, closely resembles the early morning rise of cortisol [4].…”
Section: Introductionmentioning
confidence: 99%
“…17 Kronik glukokortikoid uygulamaları, kültüre edilmiş adipositlerde ve in vivo ortamda leptin sentezini artırır. 18 Akut enfeksiyon sırasında, endotoksine ve proinflamatuar sitokinlere yanıt olarak leptin sentezi artar. 17 Büyüme hormonu eksikliğinde, muhtemelen vücut yağı artışının sonucu olarak leptin seviyesi artar.…”
Section: Lepti̇n Hormonu üReti̇mi̇ni̇ Etki̇leyen Faktörlerunclassified